Liquidity constraints, consumption, and debt repayment: Evidence from macroprudential policy in Turkey - AGARWAL, Sumit (Institutional Knowledge at Singapore Management University, 2023)
Using account-level credit card data from a large Turkish bank, we study the impact of a unique credit card policy that increases minimum payment on consumption and debt repayment. We show that the policy reduces credit card spending and debt, boosts existing debt repayment, and reduces credit card delinquency. The credit card debt of affected consumers falls on average by 50% two years into the policy’s implementation. An increase in minimum payment has a stronger effect than does a decrease of a similar magnitude. We build a benchmark life cycle model with soft liquidity constraint to explain the reduction in credit card spending.